Synthesis of Long Oxahelicenes by Polycyclization in a Flow Reactor - Nejedlý, Jindřich; Šámal, Michal; Rybáček, Jiří; Tobrmanová, Miroslava; Szydlo, Florence; Coudret, Christophe; Neumeier, Maria; Vacek, Jaroslav; Vacek Chocholoušová, Jana; Buděšínský, Miloš; Šaman, David; Bednárová, Lucie; et al. (Angewandte Chemie (International ed. in English), 2017)
A series of oxahelicenes composed of ortho/meta-annulated benzene/pyridine and 2H-pyran rings were synthesized on the basis of the cobalt(I)-mediated (or rhodium(I)- or nickel(0)-mediated) double, triple, or quadruple [2+2+2] cycloisomerization of branched aromatic hexa-, nona-, or dodecaynes, thus allowing the construction of 6, 9, or 12 rings in a single operation. The use of a flow reactor was found to be beneficial for the multicyclization reactions. The stereogenic centers present in some of the oligoynes steered the helical folding in such a way that the final oxa[9]-, [13]-, [17]- and [19]helicenes were obtained in both enantiomerically and diastereomerically pure form. Specifically, the oxa[19]helicenes beat the current record in the length of a helicene backbone. Single-molecule conductivity was studied by the mechanically controllable break-junction method with a pyridooxa[9]helicene.
Keywords: chirality; conducting materials; heterocycles; asymmetric synthesis; helical structures